Evaluation of adipocytokines and oxidative stress biomarkers in sera of hemodialysis patients - Shahad F. Obeid; Israa Abass Rashed; Mohammed S. Al-Hindawi (Journal of Advanced Biotechnology and Experimental Therapeutics)
Chronic renal failure is a condition characterized by the inability of the kidney to effectively eliminate toxins, solutes, and excess water, necessitating the use of hemodialysis. The current study aimed to evaluate adipocytokines and oxidative stress biomarkers in sera of hemodialysis patients. This study involved 60 hemodialysis patients, of whom 64% were female and 36% were male. Additionally, 40 healthy control volunteers participated in the study. Adipocytokines and oxidative stress markers were measured using the ELISA technique, whereas the spectrophotometric method measured lipid profile and renal function. The t-test, correlation, receiver operating characteristic, and logistic regression were used in the statistical analysis. Patients undergoing hemodialysis exhibited significant differences compared to healthy controls in serum concentrations of several parameters. Significantly higher levels of adiponectin (23.46 ng/mL), resistin (5.50 ng/mL), visfatin (47.0 ng/mL), and chemerin (169.0 ng/mL) were measured in patients undergoing hemodialysis as compared to healthy controls. Similarly, significantly higher levels of oxidative stress markers such as superoxide dismutase (3.78 U/mL), glutathione peroxidase (129.79 pg/mL), and malondialdehyde (4.66 mmol/L) were measured in patients undergoing hemodialysis as compared to healthy controls. In conclusion, adipocytokine parameters and oxidative stress markers have been found to be abnormal in hemodialysis patients and have an effect on atherosclerosis and heart failure progression. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 79-90]